P1464A question of gender equality. Sex-related differences in survival after primary prevention implantable cardioverter-defibrillator implantation for dilated cardiomyopathy An analysis from POLKARD. (18th June 2020) - Warchol, I; Lubinski, A; Sterlinski, M; Kowalski, O; Goscinska-Bis, K; Pytkowski, M; Mitkowski, P; Kazmierczak, J; Szwed, H; Przybylski, A; Trusz-Gluza, M; Kempa, M; et al.
Abstract: OnBehalf: POLKARD Polish ICD Registry Background: The protective effects of implantable cardioverter defibrillators (ICDs) in the primary prevention of sudden cardiac death of patients presenting with left ventricular (LV) systolic dysfunction are unequivocal. Nevertheless, female underrepresentation has been a consistent finding in all randomized controlled primary prevention ICD trials. Surprisingly, there is a vast body of literature on female primary prevention ICD patients exhibit a lower overall mortality. Purpose: Therefore, we analyzed data from a large, nationwide POLKARD registry to evaluate the effect of sex on survival after primary prevention cardioverter-defibrillator implantation for dilated cardiomyopathy. Methods: All patients enrolled in the Polish ICD Registry from 2008 to 2014 were identified. Patients were included in the study if they were designated as receiving an ICD for primary prevention of SCD after documented non-ischeamic cardiomyopathy. Kaplan-Meier survival analysis was used to assess all-cause mortality. Results: Of the 964 ICD recipients, 241 (25%) were women (mean age of 64± 0, 45 years). During a mean follow-up of 5, 53 ± 2, 48 years 32% of women and 42% of men died. Kaplan-Meier curve depicted a significantly lower mortality for women than for men (p = 0, 05). The median survival time was 6, 73 years (55 deaths per 1000 person-years) versus 6, 37 years (78 deaths per 1000 person-years) for women and men, respectively. Conclusions: In agreement with previous studies, our data indicate that primary prevention implantation rates for dilated cardiomyopathy are lower in women. However, the reasons are not entirely understood.